A new species of genus Leluthia Cameron (Hymenoptera: Braconidae) parasitizing Agrilus sp. (Coleoptera: Buprestidae) from China with a key to the East Palaearctic species - Li, Tao; Achterberg, Cornelis Van; Xu, Zhi-Chun (Zootaxa, 2015)
A new species of genus Leluthia Cameron (Hymenoptera: Braconidae), L. chinensis Li & van Achterberg, sp. nov. is described and illustrated. It was reared from Agrilus sp. (Coleoptera: Buprestidae), a twig-boring pest of Caragana korshinskii Kom. (Leguminosae) in Inner Mongolia Autonomous Region, NW China. A key to the East Palaearctic species of the genus Leluthia is provided.